Vývoj poznatků o nemoci způsobené virem hepatitidy E - Mihalčin, Matúš; Husa, Petr (Vnitrni lekarstvi, 2019)
Hepatitis E virus (HEV) infection is one of the most common causes of acute hepatitis worldwide. The Czech Republic is also a region with a natural occurrence of HEV genotype 3. Diseases caused by different genotypes have distinct clinical and epidemiological characteristics. In industrialized countries, numerous local animal reservoirs have been described and infection is considered to be zoonotic disease in these areas. The most significant route of transmission is through ingestion of insufficiently cooked meat of reservoir animals. In addition, numerous extrahepatic manifestations, even without dominant liver disease, and the possibility of chronic hepatitis in immunocompromised patients have been described. The review summarizes the current knowledge of HEV related disease and current approaches to the treatment of acute and chronic hepatitis E.
Keywords: Animals; Česká republika; hepatitis E; Humans; Zoonoses; management HEV in The Czech Republic; lidé; Genotype; Hepatitis E; zvířata; virus hepatitidy E; zoonózy; treatment of acute/chronic HEV; genotyp; Czech Republic; virus hepatitis E (HEV); hepatitida E; Hepatitis E virus